An in situ-Synthesized Gene Chip for the Detection of Food-Borne Pathogens on Fresh-Cut Cantaloupe and Lettuce - Sarengaowa,; Hu, Wenzhong; Feng, Ke; Jiang, Aili; Xiu, Zhilong; Lao, Ying; Li, Yuanzheng; Long, Ya (Frontiers in Microbiology, 2020)
Fresh foods are vulnerable to foodborne pathogens which cause foodborne illness and endanger people life safety. Rapid detection of foodborne pathogens is crucial for food safety surveillance. An in situ synthesized gene chip for detection foodborne pathogens on fresh-cut fruits and vegetables was developed. Target genes were identified and screened by comparing the specific sequences of Salmonella Typhimurium, Vibrio parahemolyticus, Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli O157:H7 from the NCBI database. Tiling array probes were designed to target selected genes in an optimized hybridization system. A total of 141 specific probes were selected from 3227 hybridization probes, comprising 26 L. monocytogenes, 24 S. aureus, 25 E. coli O157:H7 probes, 20 S. Typhimurium, and 46 V. parahemolyticus probes that are unique to this study. The optimized assay had strong amplification signals and high accuracy. The detection limit for the five target pathogens on fresh-cut cantaloupe and lettuce was approximately 3 log cfu/g without culturing and with a detection time of 24 h. The detection technology established in this study can rapidly detect and monitor foodborne pathogens on fresh-cut fruits and vegetables throughout the logistical distribution chain, i.e. processing, cleaning, fresh-cutting, packaging, storage, transport, and sale, and represents a valuable technology support the safety of fresh agricultural products.